THE EFFECT OF FINANCIAL REPORT QUALITY ON STOCK INVESTMENT DECISIONS IN PUBLIC COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE (IDX) IN 2021-2023 - Gabriele Alexandra Victory; Aminah (ZILLZELL MEDIA PRIMA, 2025)
This study aims to analyze the influence of the quality of financial statements on stock investment decisions in public companies listed on the Indonesia Stock Exchange (IDX) in 2021-2023. The population is public companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period and the sample was taken from 24 companies multiplied by 3 year periods, so that the data used was 72 data. The commonly used analysis method to test the influence between variables in this study is simple linear regression analysis. The results of the study showed a significance value of 0.017 (<a = 0.05) which means that the quality of financial statements has a significant and positive influence on investment decisions in public companies listed on the Indonesia Stock Exchange (IDX) during the 2021-2023 period. This indicates that financial statements that are prepared transparently, accurately, and in accordance with accounting standards increase investor confidence in making investment decisions.